2019
DOI: 10.1096/fasebj.2019.33.1_supplement.lb106
|View full text |Cite
|
Sign up to set email alerts
|

The Flexor Carpi Radialis Brevis: A Description of an Anomalous Wrist Flexor and Surgical Exposure Technique

Abstract: The flexor carpi radialis brevis is a rare anomalous flexor of the wrist. Surgeons occasionally encounter it intraoperatively during exposure of the volar radius. In 2 patients, this muscle was identified by its longitudinal fibers during the approach to distal radius fractures. This paper describes a surgical technique for adequately exposing a distal radius fracture when the flexor carpi radialis brevis is identified intraoperatively to preserve the innervation and arterial supply of this anomalous wrist fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The first report, described by Kang et al [ 6 ], Lee et al [ 10 ], and Hosokawa et al [ 12 ] retracted the FCRB muscle radially during surgery for distal radius fractures, and they found that FCRB did not hinder internal fixation of the distal radius fractures in any case. Other authors successfully retracted the FCRB muscle to the ulnar side [ 11 , 13 ]. Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first report, described by Kang et al [ 6 ], Lee et al [ 10 ], and Hosokawa et al [ 12 ] retracted the FCRB muscle radially during surgery for distal radius fractures, and they found that FCRB did not hinder internal fixation of the distal radius fractures in any case. Other authors successfully retracted the FCRB muscle to the ulnar side [ 11 , 13 ]. Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons must be aware of this anomalous muscle when performing surgery for distal radius fractures. However, few studies have described how to retract the FCRB [ 13 ]. We encountered seven patients with FCRB among 264 patients who underwent surgery for distal radius fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Following recognition of the muscle as a described anatomic variant, it can be managed with simple retraction, most commonly radially and/or partial detachment from its distal ulnar-most origin. 7 FCRB likely derives nervous supply from the anterior interosseous nerve, 1,8 however its supplying twig is given off proximally, therefore rendering radial retraction (as in the two illustrated cases) a valid surgical option without causing denervation.…”
Section: Discussionmentioning
confidence: 99%
“…Largely, it presents no further operative challenge than recognition intraoperatively, and a requirement for retraction to maintain appropriate exposure. 7 Here, we present two clinical case studies with appropriate illustration, to highlight this anomalous muscle and increase recognition in the age of popularised distal radius volar plating.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation